The Impact of Learning Facilities, Teacher Performance, and Competency on Implementing the Independent Curriculum in Senior High Schools in Trangkil Pati District - Aizzatin, Aizzatin; Mahmud, Amir; Utanto, Yuli (Educational Management, 2024)
The aim of this research is to determine the influence of learning facilities and infrastructure, teacher performance, and teacher competency on the implementation of the independent curriculum in junior high schools throughout Trangkil Pati District. The implementation of an independent curriculum is an educational approach that focuses on the core principles of learning, recognizing and nurturing the unique talents and interests of each child. This study employs quantitative methods. The subjects of this research were all junior high school teachers in Trangkil Pati District who were included in the basic education data. The total number of junior high school teachers is 89, which allows for the use of a saturated sampling technique. Data was collected using a questionnaire tested for validity and reliability. The research employed descriptive statistical analysis and multiple regression analysis. The results show that (1) learning facilities and infrastructure have a negative effect on the implementation of the independent curriculum by 37.8%, (2) teacher performance has a negative effect on the implementation of the independent curriculum by 24.1%, (3) teacher competence has a positive effect on the implementation of the independent curriculum by 18.6%, and (4) learning facilities and infrastructure, teacher performance, and teacher competency collectively have a positive influence on the implementation of the independent curriculum by 56.2%.